The Creation of the Tribe Ptolemais at Athens - Johnson, Allan Chester (Analecta Gorgiana, 2009)
Allan Johnson, a famous scholar of ancient civic administration, addresses the origins of the new tribe Ptolemais introduced in 3rd century BC Athens under obscure circumstances